Analysis of Positive Politeness Strategies In Wish Movie - Ni Luh Putri Ayu Febriani; Ni Wayan Sukarini; Ni Luh Sutjiati Beratha (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This undergraduate thesis is aimed to analyze the positive politeness strategies of the characters in the “Wish” movie. The collected data of this undergraduate thesis was analyzed based on the politeness theory by Brown and Levinson (1987). The method used in this undergraduate thesis was descriptive qualitative method. The results of this undergraduate thesis indicate that twelve positive politeness strategies were identified in the conversations of the characters in the "Wish" movie. These are; attend to H (Strategy 1), exaggeration (strategy 2), intensifying interest towards the hearer (strategy 3), employing in-group identity markers (strategy 4), seeking agreement (strategy 5), avoiding disagreement (strategy 6), joke (8) offering and promising (strategy 10), be optimistic (strategy 11), involving both speaker and hearer in activities (strategy 12), give or ask for reasons (13) and gifts to the hearer (strategy 15), which may include goods, sympathy, understanding, or cooperation.